2021
DOI: 10.3390/jcm10112406
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Mental Health during COVID-19 Pandemic: An Integrative Review and Implications for Clinical Practice

Abstract: The COVID-19 pandemic and measures implemented to decelerate its spread have consequences for mental health of societies. The aim of our review was to analyze depressive and anxiety symptoms in perinatal women. The search used PubMed and Web of Science databases. Most studies showed an increase in the prevalence of depression and/or anxiety symptoms. Risk factors identified in our study were mainly related to the possibility of COVID-19 infection, changes in the organization of perinatal care, social isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 73 publications
(200 reference statements)
1
69
0
1
Order By: Relevance
“…Various studies on maternal mental health during the global pandemic showed an uptrend in the symptoms of psychological distress. A recent systematic review by Suwalska et al found that the prevalence of depression and anxiety among perinatal women were as high as 56.3 and 77%, respectively ( 14 , 34 , 35 ). Current evidence also showed that the rate of psychological distress was positively correlated to the reported number of positive COVID-19 cases and related deaths ( 15 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies on maternal mental health during the global pandemic showed an uptrend in the symptoms of psychological distress. A recent systematic review by Suwalska et al found that the prevalence of depression and anxiety among perinatal women were as high as 56.3 and 77%, respectively ( 14 , 34 , 35 ). Current evidence also showed that the rate of psychological distress was positively correlated to the reported number of positive COVID-19 cases and related deaths ( 15 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Risk of COVID-19 transmission to self and fetus alongside uncertainties about deliveries, loss of household income, and domestic conflict was among the stressors which contributed toward pregnancy-related anxiety (12). Studies conducted during the first wave of the pandemic showed an increase in the prevalence of depression and anxiety among pregnant women (13)(14)(15). Wu et al found that the depressive rates were positively associated with the number of newly-confirmed COVID-19 cases and fatalities (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women struggling with fears and deprived of the supportive care provided by their partners during childbirth are in the high risk group of developing postpartum depression, anxiety, and post-traumatic stress disorder [ 25 ]. The pandemic outbreak strongly contributed to an additional source of fear—a novel SARS-CoV-2 virus with an unknown impact on maternal and neonatal health outcomes, especially among women living in areas strongly affected by COVID-19 [ 26 , 27 ]. Means of preparation for childbirth were modified—online meetings replaced the traditional antenatal classes, which were a great opportunity for face-to-face meetings with specialists and other parents [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ces constatations ont été confirmées par les résultats d´une revue de la littérature faite par Julia et al . qui indiquent une prévalence significative de la dépression (56,3%) et les symptômes d'anxiété (77%) chez les femmes enceintes pendant la pandémie de COVID-19 [ 5 ].…”
Section: Discussionunclassified